EFEKTIVITAS PENGGUNAAN MEDIA MARQUEE DALAM MENINGKATKAN KETERAMPILAN MEMBACA MEMINDAI SISWA KELAS VI SDN 81/II MUARA BUNGO - yulia oktarina; Ramaya -; Dewi Harlina (LP3M STKIP Muhammadiyah Muara Bungo, 2018)
The background of this study is the low speed reading skills of class VI SDN 81 / II Muara Bungo students. The success of reading skills can not be separated from the accuracy of the selection of learning media used in the classroom. Media Marquee (running text media) is an alternative media that can be used to improve the process and student learning outcomes. The purpose of this study was to analyze the effectiveness of Marquee's media use to improve the process and learning outcomes of speed reading for grade 6 students of SDN 81 / II Muara Bungo. This research is a classroom action research conducted in two research cycles. The research data is in the form of test results and non-test results. Furthermore, the results of this study, namely (1) an increase in the speed reading process with Marquee media with an average gain of 215.5 or in the medium category, (2) an increase in the results of speed reading learning with Marquee media with an average gain 250.25 or in the fast category. Based on the results of the research, it can be concluded that Marquee's media effectively improves the speed reading skills of class VI SDN 81 / II Muara Bungo students.